Administration Of E-Invoicing Value Added Tax(Comparative Study between Indonesia and Australia) - Riki Tenardi; Titi Muswati Putranti (Universitas Padjadjaran, 2020)
Technological changes in tax administration especially VAT have also changed the way tax authorities around the world implement e-invoice tax, one of which is Australia. The Ministry of Finance of the Directorate General of Tax (DGT) Indonesia responded to this in 2013 by creating a VAT administrative technology system called the Electronic Tax Invoice (e-Faktur). This study aims to determine the administration of Indonesian e-Faktur by looking at the Australian e-invoice as a benchmark and to find out the problems of e-Faktur in Indonesia after implementation. This research method is a qualitative method with techniques in the form of literature studies and in-depth interviews with informants. The results of this study are that the e-Faktur of the system in Indonesia is different from the understanding of the existing e-invoicing in the literature and the Australian state. Australian e-invoicing system neglects sending data in the form of digital data (PDF) and sending via email. E-Faktur was found to still have problems after its application such as access which was always problematic because of the network, the insecurity of VAT data, and the costs that still arise due to the application e-Faktur such as the still printing of documents and inefficiency. The conclusion from this study is that there are still fundamental differences between the administration of Indonesian and Australian e-invoice.